Go International Gradually: Advice to Small Businesses from Companies with Overseas Experience (Journal of Small Business Strategy (archive only), 1999)
The limited resources of small businesses often  present  unique  challenges  when  the companies try to internationalize. This paper examines the decision to enter the global arena from the viewpoint of firms who already are there. The results of a survey of such companies indicate that changes in the  external  situation  often  overcome  internal  reservations firms might have about internationalizing. Survey participants identify issues related to  risk management and the assignment of responsibility for international operations as key areas of concern, and they suggest "coping strategies" for small businesses thinking about  doing business  overseas.